Green synthesis of NiO/ZnO nanocomposites for the adsorption of various dyes - Zoya Zahid; Shaukat Saeed; Saira Arif; Muhammad Waseem; Sirajul Haq; Asad Syed; Farid Menaa; Ali H Bahkali; Ling Shing Wong (Materials Research Express, 2024)
A significant waste, including dyes in water, is generated during textile industrial processes, which causes environmental challenges. Herein, various nanocomposites (NC) of nickel oxide (NiO) and zinc oxide (ZnO) were prepared by solvothermal assisted green method where ethanolic extract of spinach leaves were used as a green source. The ultraviolet-visible (UV–vis) spectroscopy revealed that the band gap energies and absorption maxima of NiO/ZnO were 2.25 eV and 371 nm for 1:1 NC, 2.07 eV and 380 nm for 5:1 NC, and 2.02 eV and 385 nm for 1:5 NC. Ultraviolet-visible (UV–vis) spectroscopy, x-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR) were employed to investigate the optical and structural characteristics of the NCs. The XRD patterns of NiO/ZnO NCs (i.e., 1:1, 5:1, 1:5) displayed crystallite sizes of 44.6, 52.17, and 42.5 nm, respectively. Associations of different functional groups with the surfaces of NC was confirmed by FTIR. Batch method was used to conduct the NCs-mediated adsorption of methylene blue (MB), methyl red (MR), and methyl orange (MO). Furthermore, several factors, including dye concentration, contact time, and temperature that affected the sorption, are reported. Pseudo-first order and pseudo-second order kinetic models were utilized to examine the adsorption kinetics. For all the dyes studied, pseudo-first order is the one which fitted best to the kinetic data, based on regression coefficient (R ^2 ). Indeed, experimental data were found to follow the Langmuir model. The maximum uptake capacity (q _m ) of MB adsorbed on NiO/ZnO NC (1:1) was 370 mg g ^−1 which is higher compared to that of values reported in the literature. These findings report a dual method (i.e., solvothermal-green chemistry) contribute to the development of efficient and cost-effective methods for wastewater treatment and environmental remediation.